2017
DOI: 10.1177/0961000616681837
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating library signage: A systematic method for conducting a library signage inventory

Abstract: While there is much literature that directs libraries to avoid having too much or insufficient signage, there is no clear guidance on how much signage is "enough" or "too much." Conducting a signage inventory can be the first step toward determining how many signs a library needs, by establishing how many signs are in the library, of which type, and their condition. This paper proposes a ready-to-use method that any library can use to inventory its signage by adapting the inventory worksheet depending on facto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
4
0
2
Order By: Relevance
“…The staff immediately indicated that many questions asked at public service desks revolved around signage confusion and wayfinding issues. These types of questions are not surprising as the library literature demonstrates that directional questions are the major type of question asked in most libraries (Bishop & Bartlett, 2013;Mandel & Johnston, 2016).…”
Section: How Our Concierge Service Got Startedmentioning
confidence: 99%
“…The staff immediately indicated that many questions asked at public service desks revolved around signage confusion and wayfinding issues. These types of questions are not surprising as the library literature demonstrates that directional questions are the major type of question asked in most libraries (Bishop & Bartlett, 2013;Mandel & Johnston, 2016).…”
Section: How Our Concierge Service Got Startedmentioning
confidence: 99%
“…Rambu-rambu yang ada di perpustakaan juga dapat mengurangi kecemasan pemustaka dan mengurangi pengalaman buruk bagi pemustaka khusunya pemustaka yang baru menggunakan layanan perpustakaan. (Mandel & Johnston, 2016) Sedangkan menurut Andrews & Eade dengan adanya kekurangan dalam penempatan rambu-rambu yang ada di perpustakaan beresiko meningkatan kecemasan kepada pemustaka, sehingga fasilitas dalam bentuk rambu-rambu perpustakaan dapat membantu pemustaka untuk menemukan koleksi yang tersedia di perpustakaan. (Andrews & Eade, 2013) Rambu yang tidak memberikan petunjuk kepada pemustaka maka dapat menyulitkan pemustaka dalam menelusur informasi yang ada di perpustakaan, oleh karena itu dapat disimpulkan bahwa rambu-rambu yang ada di perpustakaan juga berperan dalam proses temu kembali informasi.…”
Section: Pendahuluanunclassified
“…(Beck, 1996) Kesederhanaan, dari hasil yang diperoleh dalam analisis deskriptif pemustaka menyatakan setuju atas keserhanaan dan mudah dipahaminya ramburambu yang diterapkan perpustakaan Universitas Negeri Malang dalam membantu temu kembali informasi dengan nilai 3,07. Kontinuitas, hasil analisis data menunjukkan bahwa pemustaka setuju bahwa rambu-rambu yang ada di Perpustakaan Universitas Negeri Malang berkesinambungan satu dengan yang lainnnya serta rambu-rambu di perpustakaan juga berkelanjutan dalam menuntun pemustaka memperoleh informasi yang diinginkan sehingga dapat memperjelas salah satu pendapat yang menyatakan bahwa keberadaan rambu-rambu di perpustakaan merupakan petunjuk bagi pemustaka yang dapat mengurangi kecemasan saat berkunjung ke perpustakaan khususnya bagi pemustaka yang baru mengunjungi perpustakaan tersebut(Mandel & Johnston, 2016). Dari segi konsistensi, pemusta menyatakan setuju dengan konsistensi rambu-rambu yang tersedia di Perpustakaan Universitas Negeri Malang karena memiliki tampilan yang konsisten dalam menuntun pemustaka dalam memperoleh koleksi/informasi yang ada diinginkan.…”
unclassified
“…At the beginning of our study, we performed an experiment to reveal the effects of library signs on users' search behavior. Some studies carry out experiments assessing the use of signs to locate library sources (Mandel & Johnston, ). However, no study has used the control experiment method with intervention because of the cost problem mentioned above.…”
Section: Introductionmentioning
confidence: 99%